PPP TEACHING STRUCTURE IN TEACHING GRAMMAR (Ta'limning zamonaviy transformatsiyasi, 2024)
The article introduces the PPP teaching structure (Presentation, Practice, Production) as a powerful framework for teaching grammar effectively. It highlights the importance of structured language instruction in promoting learning outcomes.The article introduces the PPP teaching structure (Presentation, Practice, Production) as a powerful framework for teaching grammar effectively. It highlights the importance of structured language instruction in promoting learning outcomes.